The Position and Role of the Supreme Court in Fostering Religious Courts as Part of the National Legal System: (Review of PERMA Number 5 of 2019) - Afiful Huda; Sari, Wulan Permata (VRISPRAAK : International Journal of Law, 2025)
This article aims to analyse the relevance of the position of the Supreme Court in relation to the Religious Courts within the national legal system, the role of the Supreme Court in the guidance and supervision of Religious Courts, and the review of the Supreme Court Regulation Number 5 of 2019 on Guidelines for Adjudicating Marriage Dispensation Applications. The approach used in this study is a normative juridical approach with a descriptive-analytical nature. The primary data source in this research is Supreme Court Regulation (PERMA) Number 5 of 2019, while secondary sources include books and articles relevant to the discussion. The data analysis technique employs content analysis. To test the validity of the data, triangulation is used along with an expanded reference base. The research results show that this "one roof" coaching aims to ensure that judicial power is exercised independently, responsibly, and without influence from the executive or other parties, thereby improving the judicial system, making it more integrated, and operating under a single command. As the Religious Courts are under the same roof as the Supreme Court, the role of judicial guidance is emphasised in Law Number 3 of 2006. Regarding technical guidance, this involves directions, particularly in the application of law by judges, carried out through various channels and methods. Meanwhile, the study of the Supreme Court Regulation Number 5 of 2019 indicates that the Supreme Court plays a key role in maintaining consistency, justice, and legal certainty in handling marriage dispensation cases in the Religious Courts, helping to preserve the integrity of the religious judicial system and ensuring that each marriage dispensation request is handled fairly and in accordance with the prevailing laws.